The concept of using physical culture as a driving force for the modernisation of the legislative sector - Filimonova, S.I.; Boldyrev, I.I.; Stebletsov, E.A.; Morozov, M.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop a model for the organisation of physical education and sport in which infrastructural, symbolic, activity-based and legal components are united by the common goal of fostering civic identity, a sense of place and a readiness to defend the homeland. Methods and structure of the study. Review of the scientific literature, comparative analysis, modelling. Results and conclusions. It has been shown that the existing legal framework only partially reflects the educational, developmental and integrative potential of physical education, which creates a systemic obstacle to the implementation of a comprehensive state policy in this area. Furthermore, the physical spaces of physical culture – school stadiums, street workout areas, fitness and health centres, and recreational zones – continue to be viewed either as ‘sports facilities’ (technical units) or as ‘leisure venues’ (service points). They are not conceptualised as territories of meaning. Yet it is precisely here—in movement, in physical and sporting activities, in overcoming challenges, and in joint effort—that fundamental patriotic attitudes are formed: a sense of home, a readiness to defend, a habit of caring for the territory, and identification with the place.